Clínica da identidade: da cosmovisão pataxó à luta por emancipação - Jörg, Simone (2017)
The focus of this research is the process of identity construction with an emancipatory sense based on the worldview and struggle for the territory of the indigenous people of Pataxó; The only ethnic group that could resist in the extreme-south of Bahia, inserted in a context of threats, persecutions and intense conflicts. Considered extinct until the beginning of the 20th century, the presence of the Pataxó on the "Discovery Coast" was noted after the known "massacre of 51", marked by destruction, violence and fire in the village of Barra Velha, the "mother village" Of the ethnic group, located in the region of Monte Pascoal, the mountain sighted by the Portuguese when they arrived in Brazil. The return of the survivors from the "mother village" massacre marks a period of intense political struggle and resistance, as well as the expansion of new villages around the Monte Pascoal National Park, the migration of some families to the sub-district of Coroa Vermelha, Administered by the municipality of Santa Cruz Cabrália. A struggle that ends after 24 years with the resumption of an area of Atlantic forest in Coroa Vermelha threatened by the capitalist exploitation and that inaugurates a new phase patagó identity with the creation of the Reserve Pataxó of Jaqueira, in a project of rescue of the memory and culture pataxó And environmental preservation. In order to meet the research objectives, we elaborated two analyzes: the first of the historical, geographic, economic, political and social aspects of the reality in which the Pataxó people are inserted, through developed academic researches and specialized literature on the process of colonization of South of Bahia in general, and of the Pataxó in particular, and in the narrative contributions of the Pataxó themselves; Located in the first part of the research indicated as Pataxó historical route. The second analysis, supported by research and academic bibliography, was empirically based on the process of recognition and territorialisation of the Reserva Pataxó da Jaqueira village, based on the proposal of the economic, cultural and environmental project of Ethnotourism and its implications for Construction of Pataxó ethnic identity with emancipatory meaning. Based on the theoretical proposal of the identity of Antonio da Costa Ciampa and the theory of ethnicity as a form of social interaction of Fredrik Barth and in the struggle for recognition of Axel Honnet. The empirical material was obtained through participant observation, the analysis of 22 semi-structured interviews, 3 interviews based on the life history narrative, and the collective meeting that involved the group of subjects of the research for the reflection and discussion of the results of the search. Interviewees between young people and adults, male and female, aged between 18 and 60 years; From elementary to higher education; Of which only two subjects were not literate. The research has shown that the struggle for recognition on both moral and social grounds constitutes the emancipatory processes that characterize the Political Identities of the indigenous Pataxó ethnic group as it claims for itself the juridical recognition of the original right to its territories in search of Better living conditions and the maintenance of their ethnic identity through the preservation of their customs and traditions. The results of the research indicated that through the self-determination of the indigenous people of the Jaqueira Pataxó Reserve in rescuing the indigenous-Pataxó-traditional character, it was possible to mark ethnic identity in the reserve's Ethnotourism services, providing the direction of economic, environmental and Cultural, inspiring the other villages with a vocation for ethnotourism to follow in the same direction, and Jaqueira became a recognized reference of cultural strengthening and environmental preservation to all other Pataxó villages. The indigenous-Pataxó-traditional character in his self-determination expresses the emancipatory sense of the group regarding the oppressions suffered by persecutions, physical and psychological tortures imputed by the surrounding non-indigenous society and the impossibility of living with their relatives and with their customs and tradition, In its own sacred territory. The character-warrior-pataxó characterizes the character-indigenous-with-rights giving rise to the character-pataxó-da-jaqueira who struggle to keep the character-pataxó-with-recognition